2006
DOI: 10.1097/00129492-200606000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Change of Phonation Control After Cochlear Implantation

Abstract: As expected, the voice quality of the prelingually deafened children was significantly worse than that of the postlingually deafened adults. After cochlear implantation, the children significantly improved their short-term and long-term F0 and amplitude variability. In adults, no significant improvement was detected. We suppose that the improvement is a consequence not only of the acquired hearing control but also of the adaptation ability of neuromuscular phonation control and the maturing of these control me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Common short‐term measurements of vocal stability—jitter and shimmer—which measure variation of pitch and loudness, respectively, within single utterances, have similarly been found to increase in hearing impaired individuals, which is consistent with decreased vocal stability. Following CI, both jitter and shimmer decrease in some prelingually deaf children, approaching normal ranges. Other studies have suggested that both jitter and shimmer in deaf children do not significantly differ from NH either before or after implantation .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Common short‐term measurements of vocal stability—jitter and shimmer—which measure variation of pitch and loudness, respectively, within single utterances, have similarly been found to increase in hearing impaired individuals, which is consistent with decreased vocal stability. Following CI, both jitter and shimmer decrease in some prelingually deaf children, approaching normal ranges. Other studies have suggested that both jitter and shimmer in deaf children do not significantly differ from NH either before or after implantation .…”
Section: Introductionmentioning
confidence: 92%
“…Following implantation, adult vF0 has been found to decrease . On the other hand, CIs have only been found to improve vAM in children . Common short‐term measurements of vocal stability—jitter and shimmer—which measure variation of pitch and loudness, respectively, within single utterances, have similarly been found to increase in hearing impaired individuals, which is consistent with decreased vocal stability.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…As demonstrated by acoustic analyses, post-lingually deaf individuals have a better phonetic control compared with prelingually deaf individuals. As suggested by the authors, better phonation quality can be the result of well-developed and stable phonation patterns (Hocevar-Boltezar et al, 2006). Nevertheless, they experience gradual degradation of their speech, likely as a result of degradation of acquired auditory phonemic goals and feedforward commands (Guenther et al, 2006;Perkell, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…Previous literature has shown that cochlear implants (CIs) may not only help hearing‐impaired patients recover their hearing but also improve their voice quality because CIs provide the patients with refined auditory feedback to monitor their voice …”
Section: Summary Of Studies On Voice Functions Of Cochlear Implanteesmentioning
confidence: 99%